An integrated permeable reactive barrier and photobioreactor approach for simultaneous removal of nitrate, phosphate and hexavalent chromium: A combined batch and continuous flow study. (August 2021) - Mittal, Akshit; Singh, Rahul; Chakma, Sumedha; Goel, Gaurav; Birke, Volker
Graphical abstract: Highlights: A novel integrated PRB and photobioreactor (PBR) system is proposed. A mixture of adsorbents for PRB and C. vulgaris microalgae for PBR is considered. PRB removed 97.2% of NO3 –, 98.4% of PO4 3− and 85% of Cr(VI). Integrated PRB-PBR system increased the Cr(VI) removal up to 98.2%. The presence of NO3 – and PO4 3− inhibits the Cr(VI) removal in PBR. Abstract: In this study, simultaneous removal of nitrate (NO3 – ), phosphate (PO4 3− ) and hexavalent chromium (Cr(VI)) from wastewater was investigated using a novel integrated filtration unit consisting of adsorbent based permeable reactive barrier (AB-PRB) and biosorption based photobioreactor (BSB-PBR). AB-PRB was comprising a mixture of low-cost adsorbents in an optimum proportion, whereas BSB-PBR carried C. vulgaris microalgae cultivated in controlled environment. The batch analysis for AB-PRB showed maximum removal efficiency of 95.7% and 98.0% for NO3 – and PO4 3−, at pH-6, whereas 84.0% for Cr(VI) at pH-4. However, continuous flow study showed decreasing trend in removal efficiency of NO3 –, PO4 3− and Cr(VI) with increasing flow rate from 10 ml min −1 to 30 ml min −1 . Further, in BSB-PBR, maximum removal of 98.2% was achieved for Cr(VI) of 1.0 mg L −1 initial concentration at 3.3 days of hydraulic retention time (HRT). This study provides a novel integrated remediation approach for efficient removal of unlike contaminants.